A Foresight Study on the Adoption of Artificial Intelligence in Recruitment and Selection in Malaysia - Ramli, Malisatasa; Eta Wahab, (Research in Management of Technology and Business, 2023)
Artificial intelligence (AI), which is one of today’s most advanced technologies is progressing rapidly with new highly developed innovations, has greatly helped in the improvement of the HR department. However, research on the adoption of Artificial Intelligence in recruitment and selection in Malaysia is very limited. Therefore, this study aims in identifying the key drivers of Artificial Intelligence (AI) adoption and to study the future image of the Artificial Intelligence adoption in recruitment and selection in Malaysia. STEEPV analysis was used to determine the key drivers or issues of Artificial Intelligence adoption in recruitment and selection in Malaysia. The analysis of STEEPV shows that technological factor is the most important driver in artificial intelligence in recruitment and selection followed by economics, social, values, political, and environmental factor. 10 merged key drivers had been identified. The impact uncertainty analysis approach had been used to identify the future image of artificial intelligence in recruitment and selection in Malaysia. A total of 384 questionnaires were distributed to the employees in HRM in Malaysia with response rate of 35.42%. The study found that data privacy and transparency and technology capability have the highest impact and the highest uncertainty. Four scenarios were proposed at the end of the study. The four scenarios were prospering of artificial intelligence, stagnant potential, scarcity of artificial intelligence and susceptibility.